2007
DOI: 10.1002/cmdc.200700047
|View full text |Cite
|
Sign up to set email alerts
|

1,2‐Mannobioside Mimic: Synthesis, DC‐SIGN Interaction by NMR and Docking, and Antiviral Activity

Abstract: The design and preparation of carbohydrate ligands for DC-SIGN is a topic of high interest because of the role played by this C-type lectin in immunity and infection processes. The low chemical stability of carbohydrates against enzymatic hydrolysis by glycosylases has stimulated the search for new alternatives more stable in vivo. Herein, we present a good alternative for a DC-SIGN ligand based on a mannobioside mimic with a higher enzymatic stability than the corresponding disaccharide. NMR and docking studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 35 publications
3
80
0
Order By: Relevance
“…They both contain a terminal mannose residue connected to a conformationally locked cyclohexanediol [67] that mimics a mannose unit -α-1,2-substituted. Both 30 and 31 bind to the Ca ++ ion in DC-SIGN binding site using the non-reducing end residue (X-ray: [68,69]), inhibit DC-SIGN binding to mannosylated BSA [70], display a measurable selectivity [68,71] against Langerin, are not cyototoxic and are active in the Ebola infection model.…”
Section: Figurementioning
confidence: 99%
“…They both contain a terminal mannose residue connected to a conformationally locked cyclohexanediol [67] that mimics a mannose unit -α-1,2-substituted. Both 30 and 31 bind to the Ca ++ ion in DC-SIGN binding site using the non-reducing end residue (X-ray: [68,69]), inhibit DC-SIGN binding to mannosylated BSA [70], display a measurable selectivity [68,71] against Langerin, are not cyototoxic and are active in the Ebola infection model.…”
Section: Figurementioning
confidence: 99%
“…A pseudo-1,2-mannobioside 1 (Figure 6), which contains a mannose unit connected to a conformationally locked cyclohexanediol to mimic 1,2-mannobioside (Mana (1,2)Man) (Reina et al, 2007). The pseudo-trisaccharide 2 mimicking the linear Mana (1,2)Mana (1,6)Man trisaccharide of the D3 arm of Man 9 , (Figure 6) was designed following the same concept .…”
Section: Boltorn-type Glycodendritic Structuresmentioning
confidence: 99%
“…DC-SIGN antagonists work by inhibiting pathogen interaction with DC-SIGN, so the very first phase of pathogen infection can be inhibited, as proven in in vitro experiments [10,41,42]. DC-SIGN antagonists may be designed as monovalent glycomimetics based on the DC-SIGN-binding oligosaccharides and their multimeric presentation [43].…”
Section: Dc-sign a Target For Anti-infective Therapymentioning
confidence: 99%
“…The most extensive work regarding the choice of the monosaccharide unit comes from the work of Bernardi and Rojo's groups from CARMUSYS [41,50,57]. In particular, they have shown that L-fucose can be incorporated in glycomimetic surrogates of Lewis-X trisaccharide to obtain even better affinity than the native trisaccharide.…”
Section: The Choice Of a Monosaccharide Unitmentioning
confidence: 99%